2015
DOI: 10.1183/16000617.00010014
|View full text |Cite
|
Sign up to set email alerts
|

Integration of interventional bronchoscopy in the management of lung cancer

Abstract: Tracheal or bronchial proximal stenoses occur as complications in 20-30% of lung cancers, resulting in a dramatic alteration in quality of life and poor prognosis. Bronchoscopic management of these obstructions is based on what are known as "thermal" techniques for intraluminal stenosis and/or placement of tracheal or bronchial prostheses for extrinsic compressions, leading to rapid symptom palliation in the vast majority of patients. This invasive treatment should only be used in cases of symptomatic obstruct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
7

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 118 publications
0
22
0
7
Order By: Relevance
“…Extraluminal Mixed airway stenting is also useful in preventing recurrence and restore the airway patency after intraluminal tumor debulking (25). The choice of techniques depends on the characteristics of stenosis, the condition of patient, available techniques and the operator's expertise ( Table 1).…”
Section: Intraluminalmentioning
confidence: 99%
See 4 more Smart Citations
“…Extraluminal Mixed airway stenting is also useful in preventing recurrence and restore the airway patency after intraluminal tumor debulking (25). The choice of techniques depends on the characteristics of stenosis, the condition of patient, available techniques and the operator's expertise ( Table 1).…”
Section: Intraluminalmentioning
confidence: 99%
“…Although they suggested that mechanical debulking under rigid bronchoscopy was probably quicker than thermal ablative therapy, there was no direct comparison of procedure time between difference methods. Combining mechanical debulking with a complementary thermal ablative procedure may be a safer choice in bleeding control (25).…”
Section: Rigid Bronchoscopy and Mechanical Debulkingmentioning
confidence: 99%
See 3 more Smart Citations